Assessing Workplace Clinic Utilization and Performance: Lessons and Implications for Care Delivery. Issue 8 (August 2020) - Kalia, Nimisha; Alfriend, Amy S.; Minor, Sebastian A.; Bernacki, Edward J.; Lavin, Robert A.; Leung, Nina; Yuspeh, Larry; Tsourmas, Nicholas F.; Tao, Xuguang (Grant)
Abstract : N/A: Many large employers utilize on-site medical clinics as a major component of their long-term healthcare cost management strategy. This study aims to quantify on-site clinic return on investment (ROI) associated with the avoidance of direct healthcare expenditures for preventive, urgent care and occupational medical services at an international beverage company. A multivariable linear regression model indicated there was a significant association between the ROI and increasing penetration rates, number of employees, and clinic age ( P < 0.0001). Over a 10-year period, while the types of services delivered changed, onsite clinics continued to demonstrate significant and increasing cost savings for this employer.